Upaya Perusahaan Danone Dalam Mempertahankan Citra Baiknya Kepada Masyarakat Indonesia - Malik, Raihan Rafi; Paksi, Arie Kusuma (Mahesa Research Center, 2023)
This research aims to find out the efforts made by Danone in maintaining its good image to the community through Corporate Social Responsibility (CSR) and media as an alternative imaging tool. The method used in this study is descriptive and uses a qualitative approach based on the research framework in the form of CSR and Multinational Corporation; the results of the study show that Danone, as a multinational company uses various auxiliary programs to the Indonesian people to maintain the good image of the company. In Indonesia, many multinational companies give a wrong impression to the surrounding community and turn into harmful stereotypes for companies, including Danone. Stereotypes that occur are wrapped around the company's name and create a bad image for multinational companies in Indonesia negative. Danone made various efforts in its CSR to restore the face of the company by helping the Indonesian people create Waste Banks, helping to create springs, improving water quality in hospitals, and using the company's social media as a tool for distributing program achievements. Various programs carried out by Danone are expected to maintain the company's good image with the Indonesian people.